Rise of Regional Logistics Hubs in Global Trade : Role of Arctic Corridor in Finland - Buyle, Christophe (Metropolia Ammattikorkeakoulu, 2015)
The proposed research concerns the engagement of the Finnish transport network into national, regional, European and global supply chains. The author was interested in studying the role of new transport corridors in trade reactivity and changes in market trends. The main target of the thesis is to understand the role of the Arctic Corridor on the implementation of Finnish development strategies. The mineral industry in Finnish Lapland and the extraction of natural resources in the Barents region will support the development of a new cross-border economic area in Finland. The corridor will connect the Baltic and the Barents Sea Regions from Kemi in Finland to Kirkenes in Norway with the aim to create new economic opportunities to Finland, Norway and the European Union. The paper identifies the strategic transport priorities of Finland through exploratory research and a cross-case synthesis of seven development strategies. As a result, the author finds five competitive advantages for Finland that arise from the Arctic Corridor. As the use of regulatory measures in management of global trade is becoming more common than using tariff barriers, regional trade agreements are progressively supplanting multilateral ones. Based on this phenomenon the thesis introduces a discussion on the rise of regional logistics hubs in global trade as a response to guarded globalization.